Which Moiety Drives Gangliosides to Form Nanodomains? - Davidović, David; Kukulka, Mercedes; Sarmento, Maria J; Mikhalyov, Ilya; Gretskaya, Natalia; Chmelová, Barbora; Ricardo, Joana C; Hof, Martin; Cwiklik, Lukasz; Šachl, Radek (The journal of physical chemistry letters, 2023)
Gangliosides are important glycosphingolipids involved in a multitude of physiological functions. From a physicochemical standpoint, this is related to their ability to self-organize into nanoscopic domains, even at molar concentrations of one per 1000 lipid molecules. Despite recent experimental and theoretical efforts suggesting that a hydrogen bonding network is crucial for nanodomain stability, the specific ganglioside moiety decisive for the development of these nanodomains has not yet been identified. Here, we combine an experimental technique achieving nanometer resolution (Förster resonance energy transfer analyzed by Monte Carlo simulations) with atomistic molecular dynamic simulations to demonstrate that the sialic acid (Sia) residue(s) at the oligosaccharide headgroup dominates the hydrogen bonding network between gangliosides, driving the formation of nanodomains even in the absence of cholesterol or sphingomyelin. Consequently, the clustering pattern of asialoGM1, a Sia-depleted glycosphingolipid bearing three glyco moieties, is more similar to that of structurally distant sphingomyelin than that of the closely related gangliosides GM1 and GD1a with one and two Sia groups, respectively.
Keywords: sfingomyeliny; glykosfingolipidy; Gangliosides; simulace molekulární dynamiky; G(M1) gangliosid; G(M1) Ganglioside; Sphingomyelins; Molecular Dynamics Simulation; Glycosphingolipids; gangliosidy